Factor Theorem-2

From Homeworkwiki

Jump to: navigation, search

Find the remainder when f(x) = x3 - 6x2 + 2x - 4 is divisible by 1 - 3x.

Solution: By remainder theorem, when f(x) is divisible by 1 - 3x, the remainder = f(1/3)

f(1/3) = (1/3)3 - 6 X (1/3)2 + 2 X 1/3 - 4

= 1/27 - 6/9 + 2/3 - 4

= 1/27 - 2/3 + 2/3 - 4 = (1 - 4 X 27)/27 = (1 - 108)/27 = - 107/27

Therefore, the required number is - 107 /27

Personal tools
McAfee SECURE sites help keep you safe from identity theft, credit card fraud, spyware, spam, viruses and online scams